Response of a pajonal (Amelichloa brachychaeta) community to frequent and high-intensity grazing in the semi-arid central region of Argentina (Semiárida, 2024)
In the central semiarid region of Argentina, caldén woodlands grasslands have been grazed with loads greater than their receptivity. They currently have large expanses of non-forage grasslands (“pajonales”), among which is Amelichloa brachychaeta, whose reproductive strategy makes management and control difficult. The work focused on determining how A. brachychaeta grasslands respond to high and frequent grazing pressure over a short period of time. In a paddock with Neltuma caldenia woodland with pajonales, 4 animal load treatments were defined to monitor the grassland for one year. 8 plots of 5000 m2 each were established in a 4 ha pajonal close to the water that had been grazed with a very high load. The load treatments were: 4, 6, 10 and 14 animals.ha-1 (n=2; N=8). Grazing was carried out when sprouts of A. brachychaeta reached 15 cm height. In each plot, floristic evaluation of the grassland was carried out in ¼ m2 plots arranged on two random lines (n=60; N=480). Total vegetation cover, litter and bare soil; cover of A. brachychaeta and perennial forages and aerial phytomass produced were evaluated. Four grazing pulses were carried out and the time the animals remained was related to the load treatment and the time of grazing, ranging between 4 and 7 days in those with the highest load and 7 and 14 days in those with the lowest load. Grazed areas presented greater richness, less vegetation cover, a greater proportion of bare soil and more litter compared to the ungrazed area. The growth rate reached its maximum before the second grazing for the 6 animals. ha-1 load, which, in addition, had the greatest availability of regrowth in the 2nd and 3rd grazing. In the grazed area, the decrease in pajonal was observed throughout the trial and the entry of other species. This type of grazing with frequent high loads over a short period of time appears to be a viable option for the management of A. brachychaeta grasslands.
Keywords: non forage species regrowth; grassland management; rotational grazing